2012
DOI: 10.1113/jphysiol.2011.223305
|View full text |Cite
|
Sign up to set email alerts
|

Nature, nurture or nutrition? Impact of maternal nutrition on maternal care, offspring development and reproductive function

Abstract: Key points• Maternal high fat nutrition during pregnancy and lactation significantly reduced maternal care during the early neonatal period; but reduced maternal care was not associated with an offspring phenotype.• Maternal high fat nutrition resulted in maternal obesity characterized by increased fat mass, hyperleptinaemia, hyperinsulinaemia.• Maternal high fat nutrition resulted in fatter offspring before puberty and advanced pubertal onset.• Adult female offspring of high fat-fed mothers have altered repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 54 publications
11
80
2
6
Order By: Relevance
“…This suggests that early life adversity exposures in Bangladeshi neighborhoods, possibly reflecting exposures to nutritional stress, infectious disease, or other yet unidentified stressors, may detrimentally impact adulthood reproductive health outcomes. In animal models, experimental studies have focused on poor maternal nutritional status in particular, showing maternal undernutrition and malnutrition were related to markers of impaired folliculogenesis, lower ovarian reserve, and increased oxidative stress in the adult offspring [63][64][65][66][67]. Consistent with these findings, in a prior study of women, maternal nutritional deprivation during famine was associated with earlier menopausal timing in the offspring [44] as was pre-pregnancy diabetes [43].…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that early life adversity exposures in Bangladeshi neighborhoods, possibly reflecting exposures to nutritional stress, infectious disease, or other yet unidentified stressors, may detrimentally impact adulthood reproductive health outcomes. In animal models, experimental studies have focused on poor maternal nutritional status in particular, showing maternal undernutrition and malnutrition were related to markers of impaired folliculogenesis, lower ovarian reserve, and increased oxidative stress in the adult offspring [63][64][65][66][67]. Consistent with these findings, in a prior study of women, maternal nutritional deprivation during famine was associated with earlier menopausal timing in the offspring [44] as was pre-pregnancy diabetes [43].…”
Section: Discussionsupporting
confidence: 75%
“…Depending on the timing of stress and the sex of the offspring, adverse offspring outcomes of prenatal stress include permanent dysfunction of the neuroendocrine axis (237) and stress responsiveness (160,208), delayed learning (160) and abnormal glucose tolerance, hyperphagia, as well as increased body weight and adiposity (111,363,387,508,546). Importantly, prenatal stress results in less maternal grooming and attention in offspring (81,418), which can have important effects on offspring behavior and metabolic phenotype (80,81,95). In keeping with these fetal/neonatematernal interactions, at least some of the abnormalities in offspring stress responsivity can be reversed by blocking the mother's stress-induced corticosterone response (32), by fostering their offspring to nonstressed dams (32) or by postnatal handling (482).…”
Section: Prenatal Stress and Offspring Obesity And Diabetesmentioning
confidence: 99%
“…However, they did not study these offspring at birth or after birth. Connor et al 14 found that the female offspring of high-fat-fed dams were lighter at birth than the offspring of control dams. However, at weaning, these pups were significantly heavier than the offspring of control dams.…”
Section: Discussionmentioning
confidence: 99%
“…12 In female rats, pubertal timing and subsequent ovarian function are influenced by the nutritional status in utero, with both maternal caloric restriction and maternal high-fat nutrition, resulting in early pubertal onset. 13 Connor et al 14 found that pups from high-fat-fed dams exhibit early puberty and irregular estrous cycles by having a prolonged and persistent estrus. All these data indicate that a poor quality of nutrition, by either excess or restriction, can disrupt the ovarian 1 Universidad de Buenos Aires, Facultad de Medicina, Departamento de Toxicología y Farmacología, Buenos Aires, Argentina 2 Universidad de Buenos Aires, Consejo Nacional de Investigaciones Científi-cas y Técnicas (CONICET), Centro de Estudios Farmacoló gicos y Botánicos (CEFYBO), Facultad de Medicina, Buenos Aires, Argentina function, especially the development and quality of oocytes.…”
Section: Introductionmentioning
confidence: 99%